Novel Four Wheel Drive Propulsion System Control Using Backstepping Strategy. (2016) - Nasri, Abdelfatah; Gasbaoui, Brahim; Fayssal, Ben Mohamed
Abstract: Recently the electrical machines are widely used in modern electric vehicle, by means new model of electric induction motors technologies are employed using in-wheel technology in on four wheels drive electric vehicle. This four wheels electric vehicle model use: static converter, modern battery storage system, in-wheel motors where the control of this multi motor system became very difficult. In this way we propose new control algorithm of one wheel motor based on backstepping control approach to control independently each in-wheel induction motors. The speed references of both of front and rear driving wheels is obtained using an electronic differential. It's permit the control independently, every driving wheel to turn at different speeds in any curve. This paper presents the study and the design of the backstepping control strategy of the electric vehicle driving wheel. Our model is simulated in MATLAB SIMULINK environment, the results obtained present the efficiency of the proposed control compared with classical types.